Közösségek hálózati kommunikációja - Vályi, Gábor (Szociológiai Szemle, 2024)
The paper aims to provide a theoretical framework for the sociological study of Computer-Mediated Communication [CMC]. Instead of investigating “Internet use” in terms of the self-fulfilling prophecy of the information-society or the applied discourse of knowledge management, this approach is focused on the real communities that communicate in virtual space. Following Barry Wellman’s approach, the paper conceptualizes on-line communication as being integral to the interaction of real social groups, rather than being distinct, virtual universe. The first section aims to provide an overview of the changing concept of community itself; the second section describes the technical specifics that make the Internet an ideal community communication/ media platform as well as the forms and distinctive characteristics of on-line communication; the last section traces the effects of CMC on the “real” life of traditional local communities.